2022
DOI: 10.3390/ijerph19105933
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Symptoms among Frontline Health Workers Post-Acute COVID-19 Infection

Abstract: Growing evidence shows that a significant number of patients with COVID-19 experience persistent symptoms, also known as long COVID-19. We sought to identify persistent symptoms of COVID-19 in frontline workers at Right to Care South Africa, who are past the acute phase of illness, using a cross-sectional survey. We analysed data from 207 eligible COVID-19 positive frontline workers who participated in a two-month post-COVID-19 online self-administered survey. The survey response rate was 30%; of the 62 respon… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 18 publications
1
12
0
Order By: Relevance
“…Overall, the proportions of healthcare workers experiencing long-term symptoms ranged from 23.1% at 6 months after infection [ 12 ] to 73% (in people with a positive nasopharyngeal swab; NPS; median 117 days since infection) [ 36 ]. The most common symptom was fatigue, [ 13 16 , 18 27 , 29 , 30 , 33 , 35 , 38 , 39 ] with proportions ranging from 4% at 8 months after COVID-19 infection [ 14 ] to 75% at 1 month after COVID-19 infection [ 21 ]. Headache reports [ 14 17 , 19 21 , 24 , 26 , 29 31 , 35 , 39 ] ranged from 0.5% at > 60 days since infection [ 20 ] to 42% at 1 month after infection [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, the proportions of healthcare workers experiencing long-term symptoms ranged from 23.1% at 6 months after infection [ 12 ] to 73% (in people with a positive nasopharyngeal swab; NPS; median 117 days since infection) [ 36 ]. The most common symptom was fatigue, [ 13 16 , 18 27 , 29 , 30 , 33 , 35 , 38 , 39 ] with proportions ranging from 4% at 8 months after COVID-19 infection [ 14 ] to 75% at 1 month after COVID-19 infection [ 21 ]. Headache reports [ 14 17 , 19 21 , 24 , 26 , 29 31 , 35 , 39 ] ranged from 0.5% at > 60 days since infection [ 20 ] to 42% at 1 month after infection [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…breathlessness, breathing difficulties, shortness of breath) [ 13 , 15 , 18 20 , 24 , 35 , 39 ] depression [ 16 , 19 , 21 , 35 , 37 ] and anxiety. [ 16 , 19 , 20 , 27 , 31 , 35 , 37 ]…”
Section: Resultsmentioning
confidence: 99%
“…Only 12.5% of employees had comorbidities, and no correlation was found between the presence of comorbidities and the need for hospitalization, which was extremely low (0.6%) in this study. Other studies in health institutions reported that up to 34% of employees with comorbidities were affected by COVID-19, with a higher hospitalization rate between 11.3% and 12.8% [ 7 , 20 , 21 , 23 ]. It is important to emphasize that the local study was conducted in the southern region of Brazil, which has health indicators such as “Hospitalization for Primary Care-sensitive conditions” that are better than the Brazilian national average.…”
Section: Discussionmentioning
confidence: 99%
“…The condition of long-term symptoms post-COVID-19 infection, known as long COVID, has generated increasing interest and discussion among researchers [ 4 , 5 , 6 , 7 , 8 ] because it affects the quality of life and health of affected individuals. The causes for the maintenance or presentation of new symptoms, even months after acute infection by SARS-CoV-2, are still not fully elucidated, with the hypotheses that they may occur because of viral persistence in the body, autoimmune mechanisms, and dysregulation of the immune system mediated by SARS-CoV-2 superantigens [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation